Implementation of Tri Hita Karana Teachings to Shape the Character of Early Children - I Wayan Redana; Mujiyono (Jayapangus Press, 2023)
Character in human life has a very important role. Character is described as a character and morals that determine people's acceptance of a person. People who have strong character, have good character and morals will be accepted in society. Vice versa, people who are immoral will be ostracized and even despised by society. Character education in Indonesia is based on nine basic character pillars. The nine pillars of basic character are: (1) love for Allah and the universe and its contents; (2) responsibility, discipline and independence; (3) honest; (4) respectful and courteous; (5) compassion, caring and cooperation; (6) confident, creative, hard working and never give up; (7) justice and leadership; (8) kind and humble, and (9) tolerance, love peace and unity. Educational institutions as places for the nation's children to receive education feel partly responsible for instilling character in their students. Hinduism as a guide for its adherents has the goal of moksartham jagadhita ya ca iti dharma, which means the realization of happiness and peace for all living things and harmony of the universe and freedom from samsara, punarbawa. Tri Hita Karana which consists of Parhyangan, Pawongan and Palemahan is a concept of the teachings of Hinduism that can help realize this goal. The application of the Tri Hita Karana concept in early childhood education activities aims to instill character values ​​in children. To understand the implementation of the Tri Hita Karana teachings to form early childhood character, the authors describe starting from the inculcation of character education values ​​at the early childhood education level and the process of implementing Tri Hita Karana at the early childhood education level. Through the application of the Tri Hita Karana concept in early childhood learning activities, the character pillars of students can be developed.